α-((4-Cyanobenzoyl)oxy)-ω-methyl poly(ethylene glycol): a new stabilizer for silver nanoparticles - Jana Lutze; Miguel A. Bañares; Marcos Pita; Andrea Haase; Andreas Luch; Andreas Taubert (Beilstein Journal of Nanotechnology, 2017)
The article describes the synthesis and properties of α-((4-cyanobenzoyl)oxy)-ω-methyl poly(ethylene glycol), the first poly(ethylene glycol) stabilizer for metal nanoparticles that is based on a cyano rather than a thiol or thiolate anchor group. The silver particles used to evaluate the effectiveness of the new stabilizer typically have a bimodal size distribution with hydrodynamic diameters of ca. 13 and ca. 79 nm. Polymer stability was evaluated as a function of the pH value both for the free stabilizer and for the polymers bound to the surface of the silver nanoparticles using 1H NMR spectroscopy and zeta potential measurements. The polymer shows a high stability between pH 3 and 9. At pH 12 and higher the polymer coating is degraded over time suggesting that α-((4-cyanobenzoyl)oxy)-ω-methyl poly(ethylene glycol) is a good stabilizer for metal nanoparticles in aqueous media unless very high pH conditions are present in the system. The study thus demonstrates that cyano groups can be viable alternatives to the more conventional thiol/thiolate anchors.